The Impact of the 2013 WHO Antiretroviral Therapy Guidelines on the Feasibility of HIV Population Prevention Trials - (:unkn) unknown (My University, 2014)
Several cluster-randomized HIV prevention trials aim to demonstrate the population-level preventive impact of antiretroviral therapy (ART). 2013 World Health Organization (WHO) guidelines raising the ART initiation threshold to CD4 <500/µL could attenuate these trials' effect size by increasing ART usage in control clusters. We used a computational model to simulate strategies from a hypothetical cluster-randomized HIV prevention trial. The primary model outcome was the relative reduction in 24-month HIV incidence between control (ART offered with CD4 below threshold) and intervention (ART offered to all) strategies. We assessed this incidence reduction using the revised (CD4 <500/µL) and prior (CD4 <350/µL) control ART initiation thresholds. Additionally, we evaluated changes to trial characteristics that could bolster the incidence reduction. With a control ART initiation threshold of CD4 <350/µL, 24-month HIV incidence under control and intervention strategies was 2.46/100 person-years (PY) and 1.96/100 PY, a 21% reduction. Raising the threshold to CD4 <500/µL decreased the incidence reduction by more than one-third, to 12%. Using this higher threshold, moving to a 36-month horizon (vs 24-month), yearly control-strategy HIV screening (vs bian-nual), and intervention-strategy screening every 2 months (vs biannual), resulted in a 31% incidence reduction that was similar to effect size projections for ongoing trials. Alternate assumptions regarding cross-cluster contamination had the greatest influence on the incidence reduction. Implementing the 2013 WHO HIV treatment threshold could substantially diminish the incidence reduction in HIV population prevention trials. Alternative HIV testing frequencies and trial horizons can bolster this incidence reduction, but they could be logistically and ethically challenging. The feasibility of HIV population prevention trials should be reassessed as the implementation of t
Keywords: African Research